Model Integratif Pembelajaran Musik Gereja Berbasis Nilai Teologis bagi Pelayan Ibadah: Studi di Kota Palangka Raya - Nadya Grestyana; Yehezkiel Ebeneser (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to analyze and develop an integrative model of church music learning grounded in theological values for worship servants in Palangka Raya. The study is motivated by the tendency of church music learning to emphasize technical skills, while theological understanding is not yet systematically integrated into ministry practices. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and documentation involving church musicians, trainers, and worship leaders. The data were analyzed using an interactive process consisting of data reduction, data display, and conclusion drawing. The findings indicate that theological values have not been fully integrated into church music learning. In response, this study proposes an integrative model consisting of three main components: internalization of theological values, enhancement of musical competence, and contextual ministry practice. The model contributes to improving both the musical quality and spiritual depth of worship services. This study offers a framework for developing more holistic and context-sensitive church music learning.